Clinical Research on Type 2 Diabetes and Its Complications - Gómez-Peralta, Fernando (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The huge prevalence of type 2 diabetes is a leading human and economic concern worldwide. The diagnosis code of type 2 diabetes includes multiple clinical phenotypes showing different degrees of obesity, fat distribution patterns, types of dyslipidemia, and characteristics of insulin resistance syndrome. In addition, subjects with type 2 diabetes could develop different clinical trajectories, with age being a critical factor in progression. The chronic complications of type 2 diabetes are a major cause of mortality and disability, and are ranked in the top places in western countries' scores. The pathophysiological heterogeneity of type 2 diabetes is not captured by the current classifications and guidelines. The potential for diabetes progression and complications developing is different depending on the type 2 diabetes cluster, which is mostly regardless of the degree of glycemic control. However, the impact on quality and life expectancy with the current therapeutic approach is not always the same for every individual. Clinical research is the key to reducing the burden of diabetes. New basic, digital, and clinical approaches are obtaining useful knowledge and designing more individualized interventions to prevent, track, and treat diabetic complications. This Special Issue is a clear reflection of this methodological evolution.